BANJARBARU PERFORMING ART CENTER YANG RESPONSIF DI ERA NEW NORMAL - Rahayu, Silfina; Oktaviana, Anna (UNIVERSITAS LAMBUNG MANGKURAT, 2022)
The design of the Performing Art Center in Banjarbaru City was the background of the lack of art container that accommodates and can only facilitate art activists on a small scale. So it can be said that the Banjarbaru City really needs a place that can accommodate art containers creativity, plus the problem in the pandemic era makes the art apparent death. The design of Performing Art Center aim to produce a design concept that can be an art container place responsive to the new normal with new normal concept and the new normal phenomenological approach, as for the appearance of the building applying concept Contemporary Architecture. Concept applied both to the arrangement of mass, circulation, facade, building technology, color and form.